An Empirical Study on Factors Influencing Consumers' Initial Trust in Wearable Commerce. Issue 1 (1st January 2016) - Gu, Zhongwei; Wei, June; Xu, Fuyuan
Abstract : This paper focuses on the factors influencing consumers' initial trust in wearable commerce. Specifically, a conceptual model for wearable commerce is created and hypotheses are developed to study the initial trust. Through a survey of 266 valid questionnaires, we carry out an empirical analysis via Structure Equation Modeling method. The results show that five proposed factors (privacy concern, trust propensity, performance expectancy, facilitating conditions, hedonic motivation) all have significant effects on initial trust in wearable commerce. The conclusion is valuable to future research on wearable commerce. Theoretical and practical implications are also presented.